Mutinus albotruncatus (Phallales, Agaricomycetes), a new phalloid from the Brazilian semiarid, and a key to the world species - Silva, Bianca Denise Barbosa Da; Cabral, Tiara Sousa; Martín, María Paz; Marinho, Paulo; Calonge, Francisco Diego; Baseia, Iuri Goulart (Phytotaxa, 2015)
A new species of the genus Mutinus has been found in the semiarid region of Northeastern Brazil. Mutinus albotruncatus is described macro- and microscopically, and is characterized by the white pseudostipe and truncated apex. Molecular and ecological data are also provided. Phylogenetic analyses, based on LSU (large subunit of nuclear ribosomal DNA) and atp6 (subunit 6 of ATP synthase) sequences, support the inclusion of this new species in the genus Mutinus. A provisional key to the species of Mutinus known in the world is proposed.